Validation of transcutaneous bilirubinometer with Kramer's scale in term babies with neonatal jaundice - A., Rajmeena; S., Chidambaranathan; R., Rajaselvan; E., Divya (International Journal of Contemporary Pediatrics, 2025)
Background: Neonatal jaundice affects a significant proportion of newborns globally and, if unrecognized or inadequately managed, may lead to severe neurological complications. In low-resource settings, clinical assessment using Kramer’s scale is often the initial approach, though its subjective nature and limited accuracy warrant further evaluation. Transcutaneous bilirubinometry (TcB) offers a non-invasive, objective alternative for estimating bilirubin levels. Methods: Across-sectional observational study was conducted involving 98 term neonates aged over 24 hours with clinical jaundice. Kramer’s zones were recorded and simultaneously TcB measurements were obtained using a handheld bilirubinometer. Data were analyzed using descriptive statistics, Pearson correlation, and one-way ANOVA Results: The majority of neonates were classified under Kramer’s zones 2 (35.7%) and 3 (32.7%). Mean TcB levels increased progressively from zone 1 (4.06 mg/dl) to zone 5 (17.65 mg/dl), with the difference being statistically significant (p=0.01). A strong positive correlation was observed between Kramer’s zone and TcB (r=0.894, p<0.01), indicating a reliable association between clinical grading and bilirubin levels. Conclusions: Kramer’s scale correlates strongly with TcB values and can be used as a reliable initial screening tool in term neonates. However, in neonates with higher Kramer’s zones, confirmatory testing using TcB or Total serum bilirubin (TSB) is recommended.